The natural patterns of self-cleaning surfaces: RIMAPS analysis of superhydrophobic leaves - Favret, Eduardo Alfredo (2012)
In the present work, an image technique based on the two-dimensional Fourier transform is introduced as a tool for describing the topographical self-cleaning pattern of the epidermis, which is composed of different features (e.g. epidermal cells and papillae, which are the microstructure or micro-pattern, and epicuticular wax, which is the nanostructure or nano-pattern). Our method allows identification of the main directions of the micro-nano structural pattern and its distribution on the x-y surface. This technique, called Rotated Image with Maximun Average Power Spectrum (RIMAPS), has recently been applied in the description of technological and biological surfaces. Therefore, the aim of the present work is to describe, by using RIMAPS, the micro-nano patterns of binary structures found on superhydrophobic (ultra non-wettable) leaves.